Revolution in Central America - Cheney, Glenn Alan. (New York : F. Watts, 1984)
Explores the causes of conflict in Central America, examining the so cial-political-historical elements of each country individually in its struggle for change.
Includes bibliographical references (p. 87) and index.
Keywords: Revolutions; Revolutions -- Central America; Central America -- History -- Juvenile literature; Central America -- Foreign relations -- United States -- Juvenile li terature; United States -- Foreign relations -- Central America -- Juvenile li terature; Central America -- History